1997
DOI: 10.1111/j.1439-0329.1997.tb00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and ultrastructural modifications to chestnut calli induced by culture filtrates of virulent and hypovirulent Cryphonectria parasitica strains

Abstract: Gallus cultures of two susceptible Castanea sativa cultivars, 'Garrone rosso' and 'Glone 71' were grown on culture medium supplemented to 50% with culture filtrates (GEs) from E4 virulent (E4-V) or E13 hypovirulent (E13-H) Cryphonectria parasitica strain, respectively. E13-H GEs caused a reduction in fresh weight and an increase in dry weight on calli of both genotypes. E4-V GEs did not induce any modification of these parameters compared with the control, but fresh weight of 'Glone 71' was reduced. Eight and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Changes involving the reduction of matter of living callus while increasing the share of dead callus were observed in tissue cultures of sweet chestnut (Castanea sativa) affected by the virulent strain of Cryphonectria parasitica. In this case, the research in dual cultures fully confirmed the in vivo observations [25]. Many studies show that virulent pathogens are stimulated by the callus in dual cultures, while saprotrophic fungi or fungi that re-colonize wood are inhibited by the callus [5,3,13,33].…”
Section: Pathogenic Organismssupporting
confidence: 71%
“…Changes involving the reduction of matter of living callus while increasing the share of dead callus were observed in tissue cultures of sweet chestnut (Castanea sativa) affected by the virulent strain of Cryphonectria parasitica. In this case, the research in dual cultures fully confirmed the in vivo observations [25]. Many studies show that virulent pathogens are stimulated by the callus in dual cultures, while saprotrophic fungi or fungi that re-colonize wood are inhibited by the callus [5,3,13,33].…”
Section: Pathogenic Organismssupporting
confidence: 71%
“…1997). In contrast, the absence of necrotic symptoms on tomato seedlings treated with H‐E13 CEs suggests that the inhibition of callus growth due to these CEs could be attributed to secondary metabolites with a growth‐regulation effect rather than a toxic action, as implied by the suppression of root differentiation observed during the phytoxicity assay and the meristematic‐like appearance of callus cells treated with culture filtrates of H‐E13 ( P IAGNANI et al. 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Growth inhibition of chestnut calli caused by V‐E4 CEs can be attributed to their toxic activity, as detected on tomato seedlings during the phytotoxicity test. A reduced concentration of phytotoxic substances is likely to explain the lack of inhibitory effect observed in callus growth exposed to V‐E4 culture filtrates ( P IAGNANI et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are in agreement with the interference with cell differentiation shown by the culture filtrates of E13 C. parasitica strain on chestnut calli of C. sativa and C. mollissima. 10 Further work is required in order to characterize the physiological effects of the compounds produced by E13 on the cultured cells of both susceptible and resistant Castanea species.…”
mentioning
confidence: 99%